The Influence of Work Facilities, Work-Life Balance and Work Discipline on Employee Performance with Job Satisfaction as an Intervening - Nurlaila, Nurlaila; Asfiah, Nurul; Dewayani, Eka Kadharpa Utama (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study aims to examine how job satisfaction mediates the relationship between work-life balance, work facilities, and work discipline on employee performance in Batu City Social Service employees. This study uses a quantitative approach. Sampling used total sampling, namely taking the entire population of 50 respondents. Data was collected through questionnaires, then processed and analyzed using Structural Equation Modeling (SEM) with the help of Partial Least Square 4.0. The results of the analysis showed that work facilities have no significant effect on job satisfaction and employee performance, work-life balance has a significant effect on job satisfaction and employee performance, work discipline has a significant effect on job satisfaction but not significantly on employee performance, and job satisfaction has no significant effect on employee performance. Job satisfaction cannot mediate the variables of work facilities, work-life balance and work discipline on employee performance. The contribution of these findings can help management to make decisions in implementing policies regarding employee discipline and programs that can support work-life balance to improve welfare and provide work facilities that support employee performance and satisfaction.